E-cigarettes and non-suicidal self-injury: Prevalence of risk behavior and variation by substance inhaled - Striley, Catherine W.; Nutley, Sara K.; Hoeflich, Carolin C. (Frontiers in Psychiatry, 2022)
Background: Nicotine and cannabis inhalation through vaping or electronic delivery systems has surged among young adults in the United States, particularly during the coronavirus disease pandemic. Tobacco and marijuana use are associated with select adverse mental health outcomes, including symptoms of major depressive disorder and suicidal behaviors. Given the need for addiction specialists to treat problematic substance use with an integrated approach, the association between non-suicidal self-injury (NSSI) and use of e-cigarettes, tobacco, marijuana, and alcohol was examined among a diverse sample of college students. Methods: Healthy Minds Study data from 47,016 weighted observations, collected from college students in the 2018-2019 academic year, was used to explore associations between NSSI-related behaviors and past 30-day use of a vaping product (nicotine or marijuana). These relationships were assessed among those using vaping products only, and then among individuals using vaping projects and alcohol, conventional cigarettes, and/or marijuana. Hierarchical logistic regression models estimating the relationship between vaping and NSSI were computed to adjust for the effects of demographic factors, symptomatology of psychiatric disorders, and concurrent use of other substances. Results: A fifth (22.9%) of respondents disclosed past 12-month NSSI; they were significantly more likely to screen positive for depression or anxiety compared to young adults without NSSI. Rates of using vaping products, conventional cigarettes, marijuana, or other substances were higher among students with NSSI even after controlling for potential cofounders. Additionally, students who used a THC-based liquid in their e-cigarettes were more likely to endorse NSSI in comparison to those who used “just flavoring”. However, young adults who vaped were less likely to disclose frequent NSSI-related behaviors than their peers who did not vape. Conclusions: These findings revealed an association between past 12-month NSSI and past 30-day vaping in a sample of young adults. Further surveillance among college populations and examination of potential sociodemographic confounders is necessary to confirm these findings and advance the substance use and addiction field.